Art comic - Thurber, Matthew (Drawn & Quarterly, 2018)
Matthew Thurber<U+2019>s Art Comic is a blunt and hilarious assault on the swirling hot mess that is the art world. From sycophantic fans to duplicitous gallerists, fatuous patrons to self-aggrandizing art stars, he lampoons each and every facet of the eminently ridiculous industry of truth and beauty. Follow Cupcake, the Matthew Barney obsessive; Epiphany née Tiffany Clydesdale, the divinely inspired performance artist; Ivanhoe, a modern knight in search of artistic vengeance, and his squire, Turnbuckle. Each artist is more ridiculous than the last, yet they are tested and transformed by the even more absurd machinations of Thurber<U+2019>s fantastical art world. Can the Free Little Pigs destroy this blighted system? Will “The Group” continue its indirect assassination of promising young artists? Can artistic integrity exist in this world amid the capitalist co-opting, petty rivalries, otherworldly portals, heavenly interventions, and murders at sea?